1993
DOI: 10.1002/kin.550250302
|View full text |Cite
|
Sign up to set email alerts
|

A relative rate study of the reaction of chlorine atoms (Cl) and hydroxyl radicals (OH) with a series of ethers

Abstract: Rate constants for the gas phase reactions of hydroxyl radicals and chlorine atoms with a number of ethers have been determined at 300 2 3 K and at a total pressure of 1 atmosphere. Both OH radical and chlorine atom rate constants were determined using a relative rate technique. Values for the rate constants obtained are as follows. CompoundHexane 5.53 2 1.55 2 4.4The above relative rate constants are based on the values of k(OH + pentane) = [3.94 2 0.981 X lo-'' and k(OH + diethyl ether) = [13.6 2 2.263 X lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 36 publications
5
18
1
Order By: Relevance
“…: RЉCl ϩ Cl 2 Table I), and our final results are obtained from the combination of the results obtained at 15 and 60 Torr. While a good agreement is observed with the rate constant values reported in this work; those obtained by Nelson et al [8] for DME, DEE, DPE, DBE, and DIPE; and those of McLoughlin et al [10] for DEE and DIPE, one could observe a disagreement with the data reported by Wallington et al [7] for DME and DEE. In all cases the data show good linearity.…”
Section: Resultssupporting
confidence: 67%
“…: RЉCl ϩ Cl 2 Table I), and our final results are obtained from the combination of the results obtained at 15 and 60 Torr. While a good agreement is observed with the rate constant values reported in this work; those obtained by Nelson et al [8] for DME, DEE, DPE, DBE, and DIPE; and those of McLoughlin et al [10] for DEE and DIPE, one could observe a disagreement with the data reported by Wallington et al [7] for DME and DEE. In all cases the data show good linearity.…”
Section: Resultssupporting
confidence: 67%
“…In the temperature range 292-390 K the agreement between the absolute and relative rate studies is good. The room temperature relative rate data of Atkinson et al (1983a), , Behnke et al (1987Behnke et al ( , 1988 and McLoughlin et al (1993), which are not shown in the Arrhenius plot in Fig. 11, are also in good agreement with these data of Atkinson et al (1982a), Klein et al (1984), Donahue et al (1998) and DeMore and Bayes (1999).…”
Section: Oh+n-hexanesupporting
confidence: 74%
“…The other measurements were performed using the relative rate technique. While a good agreement is observed with the rate constant values reported in this work; those obtained by Nelson et al [8] for DME, DEE, DPE, DBE, and DIPE; and those of McLoughlin et al [10] for DEE and DIPE, one could observe a disagreement with the data reported by Wallington et al [7] for DME and DEE. The measurements of Wallington et al were done relative to that of n-butane using k(Cl ϩ n-C 4 H 10 ) ϭ 2.25 ϫ 10 Ϫ10 cm 3 molecule Ϫ1 s Ϫ1 .…”
Section: ϫ3contrasting
confidence: 44%